2018
DOI: 10.4236/jct.2018.93029
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Chemotherapy Regimens in Unselected Patients with Metastatic Non-Small Cell Lung Cancer

Abstract: Background: Randomized clinical trials have demonstrated the benefits of chemotherapy in carefully selected non-small cell lung cancer (NSCLC) patients. How generalizable these results are to other NSCLC patients is unresolved. Methods: The outcomes of patients treated with standard chemotherapy regimens (paclitaxel/carboplatin; gemcitabine/carboplatin; pemetrexed/carboplatin; paclitaxel/carboplatin/bevacizumab) off study as first line therapy between 2002 and 2012 at our institution were compared to the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…32,33 NSCLC patients with distant metastasis are closely related to significantly reduced OS. 34 A previous study reported that LUAD occupied about 50% of all the lung cancer patients with bone metastasis. 35 LUAD individuals also displayed a 2.86-fold higher risk of brain metastases occur compared with other types of NSCLC individuals.…”
Section: Discussionmentioning
confidence: 98%
“…32,33 NSCLC patients with distant metastasis are closely related to significantly reduced OS. 34 A previous study reported that LUAD occupied about 50% of all the lung cancer patients with bone metastasis. 35 LUAD individuals also displayed a 2.86-fold higher risk of brain metastases occur compared with other types of NSCLC individuals.…”
Section: Discussionmentioning
confidence: 98%
“…As for our univariate dissection, we discovered an essential link with metastasis to the liver, adrenal glands and central nervous system, bringing about a worse prognosis of survival. Liver involvement has been shown to have a worse prognosis in different studies (Ashour Badawy et al, 2018;Liu et al, 2021). As for other researches, the bone involvement was associated with prognosis among the patients with EGFR mutations receiving TKI (LeVasseur et al, 2016;Knapp et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
“…These results are also supported by other studies. Badawy et al [28] investigated the effects of the metastatic site on the OS of patients with stage IV NSCLC. They found a statistically significant decrease in OS in patients with liver, adrenal and abdominal lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%